PERANCANGAN ADMINISTRASI PELAYANAN PADA KEDAI KOPI TUAH DOA BERBASIS WEB - Gina Ardhya Pradipta (2021)
Technology has an important role and has an impact on human activities and lives, not only individuals, but organizations or companies also feel the development of technology. With technology, it can provide effectiveness in a company's business processes to improve the quality of its services in order to compete with its competitors. However, the Tuah Doa Coffee Shop still has not utilized technology to its full potential. The Tuah Doa Coffee Shop still uses a manual system, causing the services provided to customers to take a long time. In addition, data duplication and data corruption can occur. Based on this, the author builds a web-based administration service for the Tuah Doa Coffee Shop to help the Tuah Doa Coffee Shop improve its services. The method used in system design is the waterfall method and PIECES as a system analysis method. The programming language used to build the system is PHP and the database used is MySQL. With the construction of this application, the Tuah Doa Coffee Shop has been able to record customer orders, manage a computerized menu and raw materials data and can print sales reports and also can easily manage raw materials.